Physiological and chromosomal changes of delayed harvest and stored soybean (Glycine max L. Merr.) seeds following priming - Thant, Phyu Sin (2018)
Seed deteriorations begin on the mother plant in the field and continue during storage. Basic factors influencing seed ageing are temperature, relative humidity, seed moisture content and duration of storage. Seed priming known as a pre-sowing seed treatment using natural or synthetic compounds is commonly practiced to improve seed germination and seedling emergence in a wide range of crop species. This study was undertaken to evaluate the effectiveness of seed priming treatments and post-storage priming treatments on changes in seed quality and mechanisms involved in deterioration process during field weathering and under controlled storage. For field weathering, seeds of AGS-190 and Cikurai were harvested at harvest maturity (HM), one week after HM (H1) and three weeks after HM (H3). At the time of harvest, the seeds from main stem and branches were differentiated to evaluate seed quality from different positions under field weather conditions. For storage study, the HM seeds of AGS-190 and Cikurai were stored in cold room (8±2ºC) or room temperature (25±2ºC) for 3, 6, 9, 12 and 15 months. Aged seeds of delayed harvest or stored seeds were primed with -0.8MPa PEG (Polyethylene glycol), 0.5% chitosan and water. The delayed harvested seeds from main stem and branches showed no difference in seed quality and seedling performance. Soybean seeds harvested past the HM showed adverse effects on seed physiological assessments and consequently affected seed quality. Cultivar AGS-190 was more sensitive to adverse weather conditions as shown by deterioration of seed quality at one week after HM while cultivar Cikurai with black seed coat features could maintain better seed quality up to one week after HM. Soybean seed viability and vigor considerably declined in H3 seeds with decreased activities of catalase (CAT) and superoxide dismutase (SOD) and increased accumulation of malondialdehyde (MDA) content and chromosomal aberrations. Loss of soybean seed quality in delayed harvest seeds was influenced by seed moisture content during harvest and Phomopsis sp. infection. The reactive oxygen species (ROS) production in moist seeds are much higher than dry seeds. Higher accumulation of ROS with concomitant increase in MDA content not only injured cell membrane but also caused oxidative damage to DNA of delayed harvest seeds and chromosomal aberrations.Seed priming with 0.5% chitosan and -0.8MPa PEG enhanced viability of H1 seeds in both cultivars with better germination percentage, germination index, better seedling vigour index and faster speed of germination time. Priming treatments decreased the contents of MDA and the accumulation of chromosomal aberrations in delayed harvest seeds. Recovery of germinability in field weathered seeds during priming is strongly associated with increased synthesis in CAT or SOD activities, inhibiting accumulation of lipid peroxidation and genetic damage. Significant increases in MDA content and electrical conductivity (EC) of seed leachate with increasing storage periods indicated that ageing of the seeds in room temperature (25±2ºC) caused oxidative damage to cell membrane integrity. The activities of CAT and SOD in the seeds stored at room temperature decreased with longer storage time which was favorable for ROS accumulation. Oxidative damage caused by ROS accumulation during storage at room temperature not only oxidized lipid but also damaged the nucleic acid which led to chromosomal aberrations. Deteriorative effects of seed ageing inhibited to some extent of the metabolic processes for root and shoot growth resulting longer mean germination time (MGT) and slower speed of germination, lower performance of seedling growth in aged seeds. Storing soybean seeds at 25±2ºC could maintain seed viability and vigour until 3 months. Soybean seeds stored at 8±2ºC could maintain seed viability up to 15 months and seed vigour up to 12 months. Post-storage priming with -0.8MPaPEG in 6 months stored seeds of AGS-190 resulted in higher germination percentage, germination index and better seedling performance. Moreover, post-storage priming with 0.5% chitosan and -0.8MPa PEG of seeds stored for 6-9 months improved germination percentage, germination index, seedling vigour index of cultivar Cikurai. Osmopriming with -0.8MPa PEG improved the mechanisms involved in seed germination involving CAT and SOD activities, MDA accumulation and chromosomal changes of stored seeds of AGS-190 and Cikurai. There were six different types of chromosomal aberrations observed in deteriorated seeds during field weathering and controlled storage. Under both conditions, the most abundant types of chromosomal aberrations are single bridge and sticky chromosomes. Priming with water, 0.5% chitosan and -0.8MPa PEG generally reduced single bridge and sticky types of chromosomal aberrations in both field deteriorated seeds and stored seeds. Priming not only repairs the chromosomal damage, but appears to slow down the ageing process. This study indicates that deterioration process of soybean seeds involves the production of reactive oxygen species (ROS) through depletion of antioxidant enzymes, and lipid peroxidation which ultimately interferes with cell mitotic activity. Priming improves seed quality through increase activities of antioxidant enzymes by repairing membrane damage and minimizing chromosomal damage.